The ZEB1 pathway links glioblastoma initiation, invasion and chemoresistance. Issue 8 (1st July 2013) - Siebzehnrubl, Florian A.; Silver, Daniel J.; Tugertimur, Bugra; Deleyrolle, Loic P.; Siebzehnrubl, Dorit; Sarkisian, Matthew R.; Devers, Kelly G.; Yachnis, Antony T.; Kupper, Marius D.; Neal, Daniel; Nabilsi, Nancy H.; Kladde, Michael P.; et al.
<x xml:space="preserve">Abstract</x> Glioblastoma remains one of the most lethal types of cancer, and is the most common brain tumour in adults. In particular, tumour recurrence after surgical resection and radiation invariably occurs regardless of aggressive chemotherapy. Here, we provide evidence that the transcription factor ZEB1 (zinc finger E‐box binding homeobox 1) exerts simultaneous influence over invasion, chemoresistance and tumourigenesis in glioblastoma. ZEB1 is preferentially expressed in invasive glioblastoma cells, where the ZEB1‐miR‐200 feedback loop interconnects these processes through the downstream effectors ROBO1, c‐MYB and MGMT. Moreover, ZEB1 expression in glioblastoma patients is predictive of shorter survival and poor Temozolomide response. Our findings indicate that this regulator of epithelial‐mesenchymal transition orchestrates key features of cancer stem cells in malignant glioma and identify ROBO1, OLIG2, CD133 and MGMT as novel targets of the ZEB1 pathway. Thus, ZEB1 is an important candidate molecule for glioblastoma recurrence, a marker of invasive tumour cells and a potential therapeutic target, along with its downstream effectors.